Clinical and haemato-biochemical response to epidural medetomidine and ketamine alone and in combination in Sahiwal calves - TIWARI, S K; MISHRA, O P; SHARMA, NALIN (The Indian Journal of Animal Sciences, 2014)
Epidural administration of medetomidine @ 20 Âµg/kg or ketamine @ 3mg/kg alone or in combination in 12 healthy male Sahiwal calves produced hind limb analgesia sufficient for surgical intervention. The mixture of medetomidine and ketamine produced quick onset and longer duration of analgesia in comparison to those animals where these drugs were used alone. The bradycardia, respiratory depression, ruminal stasis and other cardiopulmonary depressant effects produced by medetomidine were minimized when it was combined with ketamine. The haematological profiles of animals remained unaffected with these treatments. Significant (P<0.01) hyperglycemia of transient nature was noticed. Thus this combination can safely be used epidurally in Sahiwal calves to induce hindquarter analgesia with minimum effects on physiological and cardiopulmonary profiles.